Moment Method Boundary Conditions for Multiphase Lattice Boltzmann Simulations with Partially-Wetted Walls. (March 2015) - Hantsch, Andreas; Reis, Tim; Gross, Ulrich
We propose a lattice Boltzmann approach for simulating contact angle phenomena in multiphase fluid systems. Boundary conditions for partially-wetted walls are introduced using the moment method. The algorithm with our boundary conditions allows for a maximum density ratio of 200000 for neutral wetting. The achievable density ratio decreases as the contact angle departs from 90°, but remains of the order O(10 2 ) for all but extreme contact angles. In all simulations an excellent agreement between the simulated and nominal contact angles is observed.